2022
DOI: 10.3390/antiox11010119
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Polycyclic Aromatic Hydrocarbon (PAH)-Mediated Pulmonary DNA Adducts and Cytochrome P450 (CYP)1B1 by Dietary Antioxidants, Omega-3 Fatty Acids, in Mice

Abstract: Numerous human and animal studies have reported positive correlation between carcinogen-DNA adduct levels and cancer occurrence. Therefore, attenuation of DNA adduct levels would be expected to suppress tumorigenesis. In this investigation, we report that the antioxidants omega 3-fatty acids, which are constituents of fish oil (FO), significantly decreased DNA adduct formation by polycyclic aromatic hydrocarbons (PAHs). B6C3F1 male mice were fed an FO or corn oil (CO) diet, or A/J male mice were pre-fed with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Although PAHs are inert, CYPs that depend on metabolism can cause them to manifest their toxicities. By releasing reactive metabolites leading onto proteomic/DNA adduct generation, PAHS toxins were made manifest 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PAHs are inert, CYPs that depend on metabolism can cause them to manifest their toxicities. By releasing reactive metabolites leading onto proteomic/DNA adduct generation, PAHS toxins were made manifest 52 …”
Section: Resultsmentioning
confidence: 99%
“…By releasing reactive metabolites leading onto proteomic/DNA adduct generation, PAHS toxins were made manifest. 52 Nuclear receptors, including PXR, CAR and AhR, that are activated control the expression of the CYP gene. This research discovered a correlation between PXR and CAR mRNA levels and increased CYP1A1/2 and CYP2B1/2 mRNA following pyrene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested reduction in DNA repair ability as a result of exposure to high concentration of PAHs resulting in accumulation of albumin adducts that may lead to DNA damages and mutations, which may eventually become malignant. Recently, Zhou et al ( 2022 ) showed that the expression of some metabolic and DNA repair genes was induced by BP and inhibited by FO or omega-3 fatty acids in liver, but not lung.…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco-specific nitrosamines N-nitrosonornicotine (NNN) and nicotine-derived nitrosamine ketone (NNK) may cause reproductive damage and exhibit potent carcinogenic effects in rat and human models [ 34 , 35 , 36 , 37 ]. Polycyclic aromatic hydrocarbons (PAHs) are immunosuppressive, carcinogenic, mutagenic, and cause reproductive damage [ 38 , 39 , 40 , 41 ]. Benzene is another toxic component in cigarette smoke that causes anemia, reproductive damage, bone marrow damage, and exerts carcinogenic potential [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Cigarette Smoking and Lung Healthmentioning
confidence: 99%